Workload, Motivation, and Satisfaction's Impact on Employee Performance in Karimun's Savings and Loan Cooperative - Aran, Klementina Kona; Suhardi, Suhardi (Universitas Mercu Buana, 2024)
This qualitative research focuses on employees of savings and loan cooperatives in Karimun and Batam, comprising two Savings and Loan Cooperatives (KSP) in Karimun and five KSPs in Batam, including KSP CU Jembatan Kasih, KSP Golden Madani Sejahtera, KSP Tuah Madani Sejahtera, and KSP Pioneer Golden Raya. The study involves 100 respondents selected through purposive sampling, employing a survey method with questionnaires distributed directly to respondents. The Likert scale (1 to 5) serves as the measurement scale, and data analysis utilizes multiple linear regression with the SPSS program. The results support Hypotheses H1, H2, and H3, confirming the positive impacts of workload, work motivation, and job satisfaction on employee performance in Savings and Loan Cooperatives in Karimun. However, Hypothesis H4, proposing simultaneous influences from workload, motivation, and satisfaction, is only partially supported, with workload and work motivation exhibiting significant impacts while job satisfaction does not demonstrate a statistically significant role. These findings enhance our understanding of factors influencing employee performance in Savings and Loan Cooperatives in Karimun.